A hemispheric two-channel code accounts for binaural unmasking in humans - Jörg Encke; Mathias Dietz (Communications Biology, 2022)
A new model for sound localization based on encoding temporal fluctuations within two hemispheric channels is capable of accounting for an extensive set of psychoacoustic experiments.